Probability analysis of rainfall data for plantation of tree species in Himalayan mid-hills - Kumar, Ambrish; Singh, Anil K.; Chaturvedi, O. P. (Indian Journal of Agroforestry, 2020)
Uneven distribution of rainfall and its considerable variation from area to area and time to time, is not be very useful in predicting the time of planting of tree species in an area on the basis of average rainfall. The plantation of tree species will be of much more practical to when planted on the basis of weekly rainfall. In the present study, the weekly rainfall data of 19 years (1985-2003) of Hill Campus, Ranichauri was analysed at various probability levels and expected rainfall frequency to estimate and workout the suitable weeks for plantation of evergreen and deciduous species in mid Himalayan region. In general, the evergreen species are planted during the month of June to first fortnight of September and the deciduous species during December to February but monthly mean of rainfall does not ensure the proper establishment of seedlings planted due to its erratic distribution. Hence, weekly plan of plantation was found to be more suitable to ensure the higher survival of plants. The analysis revealed that survival performance of evergreen species would be higher if planted during 26th Â to 37th Standard Meteorological Week (SMW) as chance of rainfall occurrence in these weeks is almost 70 percent. On other hand, 6th to 8th SMW were found more suitable for plantation of deciduous tree species as probability of rainfall occurrence during this period is more than 60 per cent.